Pelatihan Budidaya Jamur Tiram Untuk Peningkatan Pendapatan Petani di Desa Bandar Sari, Padang Ratu, Lampung Tengah - ENDANG NURCAHYANI; Yulianty; Sutyarso (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Oyster mushrooms (Pleurotus spp.) are types of mushrooms that can be consumed by humans. People generally cultivate mushrooms with white fruiting bodies, so they are called white oyster mushrooms. The cultivation of oyster mushrooms is the same as the cultivation of other edible mushrooms. White oyster mushroom (Pleurotus ostreatus) is often found in traditional markets and supermarkets. The market demand for white oyster mushrooms is still very large, but the production of white oyster mushrooms is still very low. Along with the increasing popularity of oyster mushrooms in the community, causing consumer demand and the market for oyster mushrooms to continue to increase, therefore to meet these needs it is necessary to cultivate white oyster mushrooms more optimally. Based on observations in Bandar Sari Village, Central Lampung, the community has not done much white oyster mushroom cultivation, so this community service activity needs to be carried out by conducting training on oyster mushroom cultivation for the local community, it is hoped that this training can serve as an economic source for the community in the future. This training activity was held on September 17, 2021 in Bandar Sari Village, Central Lampung, aiming to provide knowledge about the types of oyster mushrooms and their benefits, oyster mushroom cultivation, and oyster mushroom processing. This activity is expected to provide skills in oyster mushroom cultivation and processing for the people of Bandar Sari Village. The results of the activity showed that people who participated in the training had increased knowledge about the types of oyster mushrooms and their benefits, oyster mushroom cultivation, and oyster mushroom processing. Keywords: Bandar Sari, Cultivation, Oyster mushrooms